Longitudinal change in TSPO PET imaging in progressive multiple sclerosis - Yeona Kang; Sneha Pandya; Nicole Zinger; Nara Michaelson; Susan A. Gauthier (Annals of Clinical and Translational Neurology, 2021)
Abstract The objective of this pilot study was to assess a 2‐year change in innate immune burden in 15 progressive multiple sclerosis (MS) patients using PK11195‐PET. Sixteen age‐matched healthy controls (HC) were included for baseline comparison. PK11195 uptake was higher in MS patients compared to HC within normal‐appearing white matter (NAWM) and multiple gray matter regions. In patients, PK11195 uptake increased in NAWM (p = 0.01), cortex (p = 0.04), thalamus (p = 0.04), and putamen (p = 0.02) at 12 months. Among patients remaining at 24 months, there was no further increase in PK11195. Our data suggest that innate immune activity may increase over time in patients with progressive MS.